2020
DOI: 10.5195/jwsr.2020.982
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Weapons and the Treadmill of Destruction in the Making of the Anthropocene

Abstract: This research analyzes the human dimensions of environmental degradation and injustice in the age of nuclear weapons. Human societies are fundamentally linked to global environmental systems and are transforming ecological conditions in dramatic ways, such that the current epoch has been termed the Anthropocene. This article highlights the human health consequences, ecological transformations, and threats to biodiversity imposed by military institutions in the Anthropocene; emphasizing how these outcomes can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Human societies are fundamentally linked to global environmental systems and are transforming ecological conditions in dramatic ways, such that the current epoch has been termed the Anthropocene (Lengefeld, 2020). The environmental damage or pollution also threatens the rights of future generations to enjoy a clean and healthy environment as an impact of the principle of ubiquity (Ali, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Human societies are fundamentally linked to global environmental systems and are transforming ecological conditions in dramatic ways, such that the current epoch has been termed the Anthropocene (Lengefeld, 2020). The environmental damage or pollution also threatens the rights of future generations to enjoy a clean and healthy environment as an impact of the principle of ubiquity (Ali, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This theory holds both in peace‐ and wartime, as the constant preparation for future conflicts tends to similarly escalate the scale and scope of military operations. A number of studies, including cross‐national analyses, have demonstrated the veracity of the core of the treadmill thesis: that the environmental impacts of national militaries are large and distinctive (Alvarez, 2016; Bradford & Stoner, 2017; Clark & Jorgenson, 2012; Givens, 2014; Jorgenson et al., 2012; Lengefeld, 2020; Smith et al., 2014; Smith & Lengefeld, 2020).…”
Section: The Military As Pollutermentioning
confidence: 99%